Agribusiness Based Coastal Tourism Development - Sulaiman, Adhi Iman; Eka Wijayanti, Irene Kartika; Risnawati, Yuli (Technium Social Sciences Journal, 2022)
The village has a lot of potential to improve the welfare of the community, such as Sodong coastal tourism in Cilacap which can be developed with Community Based Tourism. The study used descriptive quantitative methods and analysis with data collection through questionnaires, interviews, focus group discussions, observation, and documentation. Respondents were determined by a total sample of 120 people consisting of internal parties, namely the village government, tourism administrators, fishermen, farmers, and traders using Random Sampling of as many as 60 people and 60 people from outside visitors using Accidental Sampling. The research took place in Sodong Beach, Karangbenda Village, Cilacap Regency, Central Java Province of Indonesia. The results showed that the development of coastal tourism requires improving facilities and infrastructure such as electricity networks, street lighting, trash cans, and information centers. Then it requires a joint commitment to tourism managers and owners, a network of cooperation, and a more proactive government role with policies, budgets, and programs to make coastal tourism based on agribusiness and community participation.